Antibacterial activity of trimetal (CuZnFe) oxide nanoparticles - Alzahrani KE (Dove Medical Press, 2017)
Khalid E Alzahrani,1,2 Abdurahman A Niazy,3 Abdullah M Alswieleh,4 Rizwan Wahab,5 Ahmed M El-Toni,2 Hamdan S Alghamdi3 1Department of Physics and Astronomy, King Saud University, Riyadh, Kingdom of Saudi Arabia; 2King Abdullah Institute for Nanotechnology, King Saud University, Riyadh, Kingdom of Saudi Arabia; 3Prince Naif Health Research Center, Molecular and Cell Biology Laboratory, College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi Arabia; 4Department of Chemistry, College of Science, King Saud University, Riyadh, Kingdom of Saudi Arabia; 5Department of Zoology, College of Science, King Saud University, Riyadh, Kingdom of Saudi Arabia Background: The increasing resistance of pathogenic bacteria to antibiotics is a challenging worldwide health problem that has led to the search for new and more efficient antibacterial agents. Nanotechnology has proven to be an effective tool for the fight against bacteria. Methods: In this paper, we present the synthesis and traits of trimetal (CuZnFe) oxide nanoparticles (NPs) using X-ray diffraction, high-resolution transmission electron microscopy, and energy dispersive x-ray spectroscopy. We evaluated the antibacterial activity of these NPs against gram-negative Escherichia coli and gram-positive Enterococcus faecalis and then compared it to that of their pure single-metal oxide components CuO and ZnO. Results: Our study showed that the antibacterial activity of the trimetal oxide NPs was greater against E. coli than against E. faecalis. Overall, the antimicrobial effect of trimetal NPs is between those of pure ZnO and CuO nanoparticles, which may mean that their cytotoxicity is also between that of pure ZnO and CuO NPs, making them potential antibiotics. However, the cytotoxicity of trimetal NPs to mammalian cells needs to be verified. Conclusion: The combination of three metal oxide NPs (ZnO, CuO, and Fe2O3) in one multimetal (CuZnFe) oxide NPs will enhance the therapeutic strategy against a wide range of microbial infections. Bacteria are unlikely to develop resistance against this new NP because bacteria must go through a series of mutations to become resistant to the trimetal oxide NP. Therefore, this NP can combat existing and emerging bacterial infections. Keywords: nanotechnology, antibacterial agents, nanoparticles, trimetal nanoparticles, Escherichia coli, Enterococcus faecalis